2019
DOI: 10.1136/bcr-2019-229659
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-induced digital ischaemia in a professional pianist, in the absence of vasopressors

Abstract: Peripheral limb ischaemia and gangrene are devastating complications of pneumococcal sepsis. We report a 43-year-old professional pianist who presented with early sepsis and rapid development of this syndrome. No vasopressor medication was ever administered. We urgently reviewed the medical literature on a range of therapies recommended by consulting teams, to ensure he received optimal care. Based on our review and on feedback from the patient himself, we gained valuable insights into this illness and the mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…2 summarizes the typical clinical, laboratory, and temporal clinical picture of patients who develop SPG in the setting of critical illness. Since the recognition of a role of proximate shock liver in helping to explain subsequent SPG [1,2,8,40], recent SPG papers by others [90,91] have commented on the occurrence of prodromal shock liver.…”
Section: Prodromal Shock Livermentioning
confidence: 99%
“…2 summarizes the typical clinical, laboratory, and temporal clinical picture of patients who develop SPG in the setting of critical illness. Since the recognition of a role of proximate shock liver in helping to explain subsequent SPG [1,2,8,40], recent SPG papers by others [90,91] have commented on the occurrence of prodromal shock liver.…”
Section: Prodromal Shock Livermentioning
confidence: 99%
“…29 That said, limb ischemia has certainly been seen in septic patients without pressor requirement. 36 Others have suggested that microvasculature thrombosis from protein C and antithrombin deficiency associated with hepatic dysfunction (often 2-5 days before evident ischemia) are prominent factors in the pathogenesis of SPG. 27 This may align with the timeline of "shock liver" that our patient encountered.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of adult septic patients who developed SPG requiring amputation attribute vasopressor, not thrombosis, as the primary instigator, which they do defend is dose and duration‐dependent 29 . That said, limb ischemia has certainly been seen in septic patients without pressor requirement 36 . Others have suggested that microvasculature thrombosis from protein C and anti‐thrombin deficiency associated with hepatic dysfunction (often 2–5 days before evident ischemia) are prominent factors in the pathogenesis of SPG 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo retrospectivo casocontrole sobre uso de DVA e GSP demonstrou que a duração do uso de DVA não influencia o aparecimento de gangrena, mas o pico da dose pode ter papel de relevância no surgimento de gangrena, principalmente para dopamina e noradrenalina 14 . Em trabalhos descritivos de casos de GSP na literatura, os pacientes nem chegaram a fazer uso de DVA para estabelecer correlação entre causa e efeito 16,17 . Uma revisão sobre o assunto não encontrou diferença das doses e a duração de uso de DVA entre pacientes sem e com GSP 18 .…”
Section: Discussionunclassified